Original paperTHE EFFECT OF AEROBIC TRAINING ON SERUM ADIPONECTIN AND LEPTIN LEVELS AND INFLAMMATORY MARKERS OF CORONARY HEART DISEASE IN OBESE MEN - Akbarpour, M. (Biology of Sport, 2013)
The aim of this study was to investigate the effect of 12 weeks of aerobic training on the serum levels of adiponectin and leptin and on inflammatory markers of coronary heart disease in obese men. Sixteen non-athlete obese men were randomly assigned to one of two experimental groups. The experimental group underwent aerobic training consisting of three sessions per week for 12 weeks, while the control group did not participate in the training programme during the study period. Five millilitres of venous blood was taken from each participant at the beginning of the study, during week six and at the end of week 12 to measure the levels of leptin, adiponectin, C-reactive protein, interleukin-6 and tumour necrosis factor-α. The findings showed that aerobic training led to decreases in the levels of CRP (P=0.002), IL-6 (P = 0.001) and leptin (P = 0.003) and an increase in the level of adiponectin (P = 0.002) in the experimental group relative to the control group. In addition, the level of TNF-α decreased in the experimental group after the 12-week aerobic training period, although this change was not statistically significant. According to the results of this study, regular aerobic exercise decreases the potential risk of coronary heart disease by improving the plasma levels of IL-6, adiponectin, leptin and CRP Additionally, aerobic exercise can be used as effective non-pharmacological treatment to prevent diseases.